SAT-LB135 A Novel Cytoplasmic Membrane Estrogen-Mediated Biogenic Signaling Pathway - Pestell, Richard G (J Endocr Soc, 2020)
The estrogen receptor α (ERα) is known to convey both genomic and extra-genomic activities. The extra-nuclear estrogen signaling pathway is thought to involve a membrane-associated estrogen receptor (ERα), which activates PI3-kinase and Akt signaling. Maximal activation of Akt requires S473 phosphorylation. The essential G(1)-cyclin, CCND1, is a collaborative nuclear oncogene that is frequently overexpressed in cancer. D-type cyclins bind and activate CDK4/6, contributing to G(1)-S cell-cycle progression. Herein, cyclin D1 was shown to be located in the cytoplasmic membrane of patients with inflammatory breast cancer, human diploid fibroblasts and cancer cell lines (breast, prostate). The extra-nuclear vs. nuclear E(2)-induced signaling pathways can be distinguished using 17β-estradiol linked to a dendrimer conjugate (EDC), which excludes estradiol from the nucleus. In contrast with the nuclear-localized form of cyclin D1 (cyclin D1(NL)), the cytoplasmic membrane-localized form of cyclin D1 (cyclin D1(CML)) was sufficient to induce phosphorylation of the serine threonine kinase Akt (Ser473) and augmented extra-nuclear localized 17β-estradiol dendrimer conjugate (EDC)-mediated phosphorylation of Akt (Ser473). Cyclin D1(CML) was sufficient to induce G(1)-S cell-cycle progression, cellular proliferation, colony formation. In contrast with cyclin D1(NL), the cyclin D1(CML) induced transwell migration and the velocity of cellular migration. Together these studies suggest distinct subcellular compartments of cell cycle proteins may convey distinct functions. The major adjuvant therapy for the ~70% of ERα expressing human breast cancer involves anti-estrogen therapy and the ERα/PI3K/Akt complex pathway is hyperactivated in aggressive breast tumors. The non-genomic actions of E(2)/ERα, mediated via cyclin D1(CML) may provide an important additional target. References. 1. 2. Casimiro MC et al Mol Endocrinol. 2013;27(9):1415-28. Di Sante, G, Expert Rev Anticancer Ther. 2019 Jun 20:1-19.